Executive Incentives on Tax Avoidance and Their Impact on Firm Value - Wawan Cahyo Nugroho (Jurnal Manajemen Dan Akuntansi Medan, 2026)
Latar belakang: This study focuses on examining the effect of executive incentives on tax avoidance and firm value, the effect of tax avoidance on firm value, and the effect of executive incentives on firm value mediated by tax avoidance. Metode penelitian: The population in this study were pharmaceutical companies listed on the Indonesia Stock Exchange in 2020-2024. Sampling using purposive sampling obtained 10 samples. Hasil penelitian: The results of this study indicate that executive incentives affect tax avoidance because executives as operational leaders of the company will be willing to implement tax avoidance policies only if they also benefit from such actions, while executive incentives do not affect firm value due to the compensation structure is not well designed to encourage optimal performance. Tax avoidance does not significantly affect firm value because investors generally prefer to invest their investments in companies with stable or high profits. Tax avoidance does not mediate the relationship between executive incentives and firm value. Kesimpulan: Providing incentives only encourages executives to engage in opportunistic tax avoidance, but this action is not responded to positively by the market and is unable to increase the company's value.